2018
DOI: 10.1152/jn.00834.2017
|View full text |Cite
|
Sign up to set email alerts
|

Higher order, multifeatural object encoding by the oculomotor system

Abstract: Previous behavioral and physiological research has demonstrated that as the behavioral relevance of potential saccade goals increases, they elicit more competition during target selection processing as evidenced by increased saccade curvature and neural activity. However, these effects have only been demonstrated for lower order feature singletons, and it remains unclear whether more complicated featural differences between higher order objects also elicit vector modulation. Therefore, we measured human saccad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 79 publications
1
14
2
Order By: Relevance
“…Saccade curvature indicated that the magnitude of inhibition increased as distractors became increasingly dissimilar to the target, which we have observed previously using the same stimulus set (17). This is the opposite pattern of results observed in previous behavioral studies of saccade curvature using opponent color singletons (19,20).…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…Saccade curvature indicated that the magnitude of inhibition increased as distractors became increasingly dissimilar to the target, which we have observed previously using the same stimulus set (17). This is the opposite pattern of results observed in previous behavioral studies of saccade curvature using opponent color singletons (19,20).…”
Section: Discussioncontrasting
confidence: 79%
“…Critically, the secondary excitatory epoch occurred before the inhibitory processing for the low and intermediate-similarity distractors, which suggests that the protracted excitatory epoch encoding highsimilarity distractors does not merely reflect a delayed onset of inhibition. As distractor identity could be decoded from the magnitude and duration of excitatory processing related to the distractor onset, this suggests that the oculomotor system dynamically receives preprocessed object representations from relevant visual modules and encodes these objects as dynamically reweighted oculomotor vectors, as we have argued previously (17,18,22).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations